1999
DOI: 10.1155/1999/812476
|View full text |Cite
|
Sign up to set email alerts
|

Acute Respiratory Distress Syndrome: 30 Years Later?

Abstract: Acute respiratory distress syndrome (ARDS) was first described about 30 years ago. Modern definitions and statements have recently been proposed to describe ARDS accurately, but none is perfect. Diffuse alveolar damage is the basic pathological pattern most commonly observed in ARDS, and the term includes permeability edema. The alveolar epithelium of the alveolar-capillary barrier is clearly a key component requiring repair, given its multipotent functional activity. Lung inflammation and neutrophil accumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
27
0

Year Published

2002
2002
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 114 publications
(113 reference statements)
0
27
0
Order By: Relevance
“…A ctivation of polymorphonuclear leukocytes has long been implicated in the development of acute respiratory distress syndrome (ARDS), 3 characterized by gas exchange abnormalities and pulmonary edema formation due to increased lung endothelial and epithelial permeability (1)(2)(3)(4). Hydrogen peroxide (H 2 O 2 ), a reactive oxygen species, is an established polymorphonuclear leukocyte-derived mediator of epithelial injury.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A ctivation of polymorphonuclear leukocytes has long been implicated in the development of acute respiratory distress syndrome (ARDS), 3 characterized by gas exchange abnormalities and pulmonary edema formation due to increased lung endothelial and epithelial permeability (1)(2)(3)(4). Hydrogen peroxide (H 2 O 2 ), a reactive oxygen species, is an established polymorphonuclear leukocyte-derived mediator of epithelial injury.…”
mentioning
confidence: 99%
“…In animal models and under cell culture conditions, various clinical features of ARDS may be reproduced by endotoxin (LPS) released from cell walls of Gram-negative bacteria (1)(2)(3). The microcirculatory disturbances with subsequent cellular injury and loss of organ function induced by LPS in intact animals have been attributed to the activation of inflammatory cells and strong inflammatory mediator generation.…”
mentioning
confidence: 99%
“…At least in its early stages, ARDS represents the pathologic state of diffuse alveolar damage (DAD). [6][7][8] There is damage to both endothelial and epithelial layers 6,[8][9][10][11] of the alveolar-capillary membrane with resultant edema and alveolar flooding rich in proteins and hemorrhage, leading to hyaline membrane formation and fibrosis. 6,10 These changes can overlap and evolve over hours to days and result in a loss of the barrier and gas exchange functions of the lung (Table 15-2).…”
Section: Pathophysiology and Clinical Features Of Ardsmentioning
confidence: 99%
“…[6][7][8] There is damage to both endothelial and epithelial layers 6,[8][9][10][11] of the alveolar-capillary membrane with resultant edema and alveolar flooding rich in proteins and hemorrhage, leading to hyaline membrane formation and fibrosis. 6,10 These changes can overlap and evolve over hours to days and result in a loss of the barrier and gas exchange functions of the lung (Table 15-2). 6,8,[12][13][14] The clinical consequence is a severe heterogeneous injury to the lung that results in refractory hypoxemia and decreased lung compliance.…”
Section: Pathophysiology and Clinical Features Of Ardsmentioning
confidence: 99%
“…Furthermore, there is no recognized prophylactic measures for human PFIB exposure although animal studies have indicated that increased pulmonary concentrations of free radical scavengers containing thiol groups may be of value and N-acetylcysteine has been found to be effective 6) . Early administration of corticosteroids, as used for phosgene, seems to be the only clinical recommendation for pharmacological intervention even though proof of their beneficial effects is still lacking in general 7) . When comparisons are made concerning the molecular structure 8,9) , the time course of ALI after the inhalation e x p o s u r e 10, 11) a n d m a n y o t h e r t o x i c o l o g i c a l characteristics [12][13][14] between PFIB and phosgene, it seems clear to us that both primary (direct) injury by the chemical itself and secondary (indirect) injury, possibly mediated by a later signal cascade network, are the two key aspects of PFIB inhalation induced ALI.…”
mentioning
confidence: 99%